Problem of land banking centre in rural areas near to the city: discussion through the example of basque country - Juan Cruz Alberdi Collantes (Boletín de la Asociación de Geógrafos Españoles, 2016)
Land Management Centres, call Land Banking too, born in Spain during the eighties but two decades later the Asturias model is the unique which marks the way to reference for the other. Later there are growing new initiatives which are taking the law and administration structure of Asturias. But their possibilities and reality are different, especially the access tothe ground and, therefore, the results are different. In this paper we study the Land BankingCentres in Basque Country. The first results show the difficulty to move private land and, as consequence, the necessity to move public land to development farm projects. Besides, this example shows the way to development land banking models in rural areas near to the city.